Women Art Educators of the Design Workshop and the Advancement of Progressive Art Education. (3rd July 2022) - Fowler, Cynthia
Abstract : Ralph Pearson's Design Workshop was a center of progressive art education in New York. However, based on the correspondence courses that he developed, he was able to reach artists and art educators across the United States. Women artists and art educators dominated his courses and went on to play an important role in spreading progressive art education ideas within their local communities. Recognition of the contributions of these Design Workshop women, as well as other women studying modern art education in similar venues, is essential in moving away from constructions of art education history that have been overly determined by a disproportionate focus on modern art education in large urban areas, and doing so will lead to a more comprehensive history that is inclusive of local communities as important spaces of experimentation.